Fundamentals of clinical trials - Friedman, Lawrence M; Furberg, Curt; DeMets, David L (Springer, 1998)
This text is intended for the clinical researcher who is interested in designing a clinical trial and developing a protocol. It is also of value to researchers and practitioners who must critically evaluate the literature of published clinical trials and assess the merits of each trial and the implications for the care and treatment of patients. The text uses numerous examples of published clinical trials from a variety of medical disciplines to meaningfully illustrate the fundamentals. Technical design issues such as sample size are considered, but the technical details have been suppressed as much as possible through the use of graphs and tables. While the technical material has been kept to a minimum, the statistician may still find the principles and fundamentals presented in this text useful both in a consulting and teaching capacity.
Keywords: management, organizace a řízení zdravotnictví; Clinical Trials as Topic; klinické zkoušky jako téma; výzkumný projekt; Research Design